1981
DOI: 10.1111/j.1471-0528.1981.tb00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Small‐for‐dates Twin Fetus by Ultrasound

Abstract: Summary As methods for identifying the small‐for‐dates fetus in twin pregnancies, serial ultrasonic cephalometry and a new two‐stage ultrasound examination schedule have been evaluated and compared. Serial cephalometry is associated with technical and interpretative problems, and only 24 (56 per cent) of 43 small‐for‐dates fetuses in 66 retrospectively studied twin pregnancies showed detectably abnormal biparietal diameter growth. The two‐stage schedule comprises an accurate assessment of gestational age in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The detection of chronic placental insufficiency by repeated measurements of the biparietal diameter of the fetal head is very difficult on account of the position of the children, particularly in multiple pregnancies [8,9,19,24]. Our studies confirmed these results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The detection of chronic placental insufficiency by repeated measurements of the biparietal diameter of the fetal head is very difficult on account of the position of the children, particularly in multiple pregnancies [8,9,19,24]. Our studies confirmed these results.…”
Section: Discussionsupporting
confidence: 94%
“…With repeated measurements of the biparietal diameter, the sensitivity to detect growth retardation in one of the fetuses was 56% [24].…”
Section: Introductionmentioning
confidence: 98%
“…The same applies to the comparison of the sensitivities of Doppler velocimetry (60%) and the nonstress test (10%) regarding the identification of an intrauterine asphyxia [15]. The problems of fetal biometry in multiple gestation [16,17] and the small predictive value of the nonstress test are well known from other studies [18,19].…”
Section: Introductionmentioning
confidence: 90%
“…Estimation of fetal size by abdominal palpation is made more difficult by the presence of the other twin, and biochemical investigation is of little value because only the combined endocrine output from both fetoplacental units can be assessed (Westergaard et al 1985). Complex ultrasound measurements of twin fetuses may be highly sensitive in predicting SGA babies (Neilson 1981), and early reports of Doppler ultrasound indicate potential usefulness (Farmakides et al 1985;Giles et al 1985;Nimrod et al 1987) but these techniques are not yet widely available. Tape measurement of symphysis-fundal height is becoming a widely used method to identify the SGA fetus in singleton pregnancies with reported sensitivities ranging between 55% (Rosenberg et al 1982) and 89% (Belizan etal.…”
mentioning
confidence: 99%